2018
DOI: 10.29245/2578-2967/2018/6.1154
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Web Portal Use by Oncology Patients

Abstract: Background: Patient portals and other Internet-based technologies have been increasingly used to improve cancer care coordination. Patient portals may introduce special considerations in oncology populations where longitudinal outpatient care is often more intensive than in most other specialties. Methods: This article, which is based upon bibliographic searches in PubMed, reviews the literature on web portal use by cancer patients. Articles published in English from 2000 to August 2018 were identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Also surprising is that time since cancer diagnosis was not associated with satisfaction using this communication modality to communicate with oncology clinicians. A recent study found that patient portals are commonly used by patients with an existing cancer diagnosis (i.e., younger, white, and higher socioeconomic status) to review test results [ 15 ]. Efforts to further segment patients with cancer according to their point on the care continuum, beyond simply date of diagnosis, will be important to understand the nuances of cancer care and secure message use.…”
Section: Discussionmentioning
confidence: 99%
“…Also surprising is that time since cancer diagnosis was not associated with satisfaction using this communication modality to communicate with oncology clinicians. A recent study found that patient portals are commonly used by patients with an existing cancer diagnosis (i.e., younger, white, and higher socioeconomic status) to review test results [ 15 ]. Efforts to further segment patients with cancer according to their point on the care continuum, beyond simply date of diagnosis, will be important to understand the nuances of cancer care and secure message use.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis is adjusted for gender (male, female), age (<55 years, 55 to 64 years, 65 to 74 years, 75 years and older), race/ethnicity (non-Hispanic White, non-Hispanic Black, Hispanic, non-Hispanic Asian/other), income level (<$35,000, $35,000-$99,999, ≥$100,000), education level (less than high school, high school graduate, some college, college graduate or more), and health insurance status (private, Medicare, Medicaid, or dual coverage). Previous research has shown that these variables have an impact on access and use of patient portals [ 20 , 46 , 47 ]. In this analysis, we also accounted for time since diagnosis of cancer (less than 1 year, 2 to 5 years, 6 to 10 years, ≥11 years) as it can also impact a patient’s information-seeking needs [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Canadian Cancer Society [ 13 ] predicts that approximately 1 in 2 Canadians will be diagnosed with cancer in their lifetime, and about 1 in 4 will die of the disease. With the steady year-on-year increase in cancer diagnoses, online patient portals are becoming more desirable to augment the coordination of care for oncology patients [ 14 ]. Cancer treatment and the cancer diagnosis, in and of itself, result in a wide range of self-management challenges, such as monitoring side effects and scheduling numerous medical appointments.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer treatment and the cancer diagnosis, in and of itself, result in a wide range of self-management challenges, such as monitoring side effects and scheduling numerous medical appointments. Oncology patients have a keen interest in portals, as they require comprehensive health information, have blood work done regularly, and often are, or are expected to be, active participants in managing their condition [ 14 , 15 ]. They report that using portals allows them to feel more in control of their situation, be better prepared for medical appointments, and provides them with the opportunity to advocate for their needs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%